MENINGKATKAN PRESTASI BELAJAR SENI BUDAYA MELALUI TUGAS MANDIRI PADA MATERI ENSAMBEL MUSIK (Harmonia: Journal of Arts Research and Education, 2009)
This study aims to find out and describe the extent to which provision of independent tasks canimprove learning achievement at the Cultural Arts ensemble material. The method used in thisstudy is the class-action research using a descriptive approach to quantitative and qualitative.The model was used with step cycle: planning, action, observation and reflection. Data wasanalyzed in each cycle of observation and reflection. The results showed that: independent taskmethod can enhance students' learning achievement 8th-grade students of Watumalang JuniorHigh School, was seen from the increase in the percentage of success from all cycles. In cycle I,the success of students only 10.7% good, cycle II, the success of students increased to 82.1% good,and the third cycle of increased student success more to 96.4%. Suggestions in this research are:(1) Teachers can socialize independent assignment method and implementing these methods inlearning and Cultural Arts as far as the condition of their students with students who have thecondition in this study that students have the responsibility, discipline, willingness andenthusiasm for learning high.Kata Kunci : prestasi belajar seni budaya, tugas mandiri, ensambel musik.